The effects of dashboard design form on driving information reading performance under different time pressures - Liu, Yunxing; Shen, Zhangfan (Frontiers in Psychology, 2025)
In scenarios where driving decisions must be made rapidly, an optimally designed dashboard is crucial for maintaining driver concentration and facilitating precise decision-making. This study examines the influence of four principal aspects of dashboard design—graphical form, scale precision, indicator type, and external time pressure—on users' performance in reading information. Thirty postgraduate students engaged in a visual information recognition task comprising 288 trials, during which reaction time (RT) and absolute error (AE) were documented as dependent variables. Results showed that under both stringent (2,000 ms) and moderate (4,000 ms) time constraints, dashboards incorporating a semicircular or horizontal bar design, along with a progress-bar-type indicator and low scale precision (10), resulted in significantly faster RT and reduced AE. Conversely, circular dashboards generally exhibited subpar performance, particularly under increased time pressure. Additionally, a notable interaction between graphical form and time pressure was observed, indicating that circular dashboards were particularly susceptible when time was restricted. These findings provide practical guidance for designing driver-machine interfaces in safety-critical environments and concurrently contribute to theoretical developments in visual perception, human-computer interaction, and applied design methodologies.